The RO-BG 2 project continues: Investigating the opportunities to reduce the use of the ten-t network in the cross-border region Romania - Bulgaria by optimizing the transport of goods and passengers as well as the development of a common mechanism to support the intermodal connection 2014 - 2020, 2021 - 2025 - Cristiana Sirbu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The Romania - Bulgaria project, Interreg V-A 2014-2020 Program was started on February 12, 2015 (RO - BG 1) and financed by the EU from the European Regional Development Fund with the aim of developing the border area between the two countries by financing of joint projects, and in the period 2021-2025 we proposed to continue the research through a new Project Romania - Bulgaria, Interreg V-A Program. The strategic framework of the program brings an extraordinary perspective for regional development that is based on concrete and measurable results with the ability that in the next 25 years, the two countries, Romania and Bulgaria, offer the most modern infrastructure and perspectives to settle the active population from the 18-55 age segment, benefiting from numerous living and working conditions and at the same time the growth of competitive and sustainable communities through the efficient use of resources and the capitalization of growth opportunities related to belonging to the Danube and Black Sea regions. Our project is a very well-articulated guide that will continue the documentation that will also help to start the work necessary to build an economic interconnection platform to ensure the consistency of the 12 states located between the Adriatic, Baltic and Black Seas with what is meant by the Danube Corridor. The main economic fields in which the I3M member countries are interested are defined by three major pillars: Energy, Transport, Digitization. We are strongly engaged, both I, in the position of coordinator, Prof. Dr. Eng. Cristiana Sirbu, president of the GIEDD Foundation, as well as our partners from the Association of Danube Municipalities "Dunæarea" in Bulgaria, to correlate the data processed through the Romania - Bulgaria Project 1, Interreg Program V-A 2014-2020 with a new Project Romania - Bulgaria 2 2021 - 2025 which we propose to connect the main Danube corridors, as well as the Black Sea to the I3M Mega Project.
Keywords: R0; R4; 330; energy; transport; digitization; infrastructure; Danube corridors